On the Well-Posedness of a Fractional Model of HIV Infection - Mohamed Jleli; Bessem Samet (Journal of Function Spaces)
In this paper, we are concerned with the well-posedness of a fractional model of human immunodeficiency virus infection. Namely, using Grönwall’s lemma and Perov’s fixed point theorem, we obtain sufficient conditions for which the considered model admits a unique solution.